2011
DOI: 10.1074/jbc.m111.220574
|View full text |Cite
|
Sign up to set email alerts
|

The Atypical Response Regulator Protein ChxR Has Structural Characteristics and Dimer Interface Interactions That Are Unique within the OmpR/PhoB Subfamily

Abstract: Typically as a result of phosphorylation, OmpR/PhoB response regulators form homodimers through a receiver domain as an integral step in transcriptional activation. Phosphorylation stabilizes the ionic and hydrophobic interactions between monomers. Recent studies have shown that some response regulators retain functional activity in the absence of phosphorylation and are termed atypical response regulators. The two currently available receiver domain structures of atypical response regulators are very similar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
33
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(40 citation statements)
references
References 50 publications
5
33
0
2
Order By: Relevance
“…However, the DNA binding domains of ChxR appear to have tandem symmetry (head-to-tail) based upon the SAXS analysis presented herein, as well as their monomeric state and reduced DNA binding affinity in the absence of the receiver domain. This matches the orientation of the DNA sequence motif (direct repeat) recognized by ChxR [13]. The resulting orientation is not unexpected for an OmpR/PhoB subfamily member, and was recently highlighted by Bachhawat et al [73].…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…However, the DNA binding domains of ChxR appear to have tandem symmetry (head-to-tail) based upon the SAXS analysis presented herein, as well as their monomeric state and reduced DNA binding affinity in the absence of the receiver domain. This matches the orientation of the DNA sequence motif (direct repeat) recognized by ChxR [13]. The resulting orientation is not unexpected for an OmpR/PhoB subfamily member, and was recently highlighted by Bachhawat et al [73].…”
Section: Discussionsupporting
confidence: 79%
“…The active state is stabilized by phosphorylation, which enhances DNA binding affinity, and makes dimerization through the α4–β5–α5 interface energetically favorable. Atypical RRs exist in a constitutively active, dimeric state as demonstrated by previous studies on ChxR [13], [17] and HP1043 [12], [14], [52]. Recent studies by Barbieri et al demonstrated that interdomain interfaces stabilize the inactive state and inhibit phosphotransfer-mediated activation [5].…”
Section: Discussionmentioning
confidence: 88%
“…These two conserved amino acids are referred to as “switch residues” and are used as traditional indicators of conformational state for rec domains . Some studies have also implicated the aromatic residue (Phe/Tyr/His) as a factor in rec domain dimerization, due to its location in the center of a common dimerization interface . In CheY, these switch residues are Thr87 and Tyr106.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the atypical receiver domains of several orphan RRs (7,22,23) were shown to be generally similar to the typical receiver domains in their amino acid sequences and three-dimensional structures but lacked one or more residues of the highly conserved active site quintet (22,24). Because the GlnR from actinomycetes other than streptomycetes (see Fig.…”
mentioning
confidence: 99%